Shear stress, inflammation and Atherosclerosis - Rob Krams; Simon Cuhlmann; Nicolas Foin; Paul Evans (Artery Research, 2010)
Background: Atherosclerosis is the disease with one of the largest mortalities of the Western world. An important cause of this high mortality rate is rupture of atherosclerotic plaques and subsequent total blockage of the vessel by thrombus. Because, plaque rupture has been associated with a distinct plaque phenotype there is a growing need for understanding the pathogenesis of plaque composition. In this manuscript, we will discuss the new hypothesis that blood flow and lipid driven inflammation are intimately related to each other and that shear stress induced expression of chemokines and the resulting coordinated homing of inflammatory cells influence plaque composition in such a way that vulnerable plaque may be induced. As vulnerable plaques are intimately related to the high mortality of atherosclerosis, it re-emphasis the important role blood flow has in atherosclerosis.